Ochrona wierzycieli spółki z o.o. poprzez osobistą odpowiedzialność jej wspólników. Koncepcja odpowiedzialności przebijającej i nadużycia formy prawnej spółki w prawie niemieckim i polskim - Wiórek, Piotr Marcin (2016)
Within the ambit of the thesis herein submitted – which is comparative in its character - the concept of piercing liability (Durchgriffshaftung), which has been developed in German doctrine and case-law, along with analogous concepts which are being developed in Polish doctrine - of an abuse of a legal form of a company, abuse of legal personality and abuse of resorting to a form of a legal person (insofar as they pertain to liability of members of a sp. z o.o. company in regard to its creditors), have been subjected to critical analysis. Theoretical and dogmatic grounds for liability of members of a sp. z o.o. company vis-à-vis its creditors under the concept of piercing liability have been presented hereunder in detail, alongside respective groups of cases justifying piercing liability that have been developed by German doctrine and case-law (the instances of ‘piercing’), that, at the same time, could be described as instances of an abuse of a legal form of a company. A critique of the concept of piercing liability that was voiced in German doctrine and case-law and in Polish doctrine has been presented as well. For the purposes of the contextual and functional comparative analysis undertaken herein, the German legal order has been selected as a point of reference, while the Polish legal order has been one of destination. The purpose of the thesis was namely to answer the question whether the concept of piercing liability would be possible for reception into Polish company law, and whether its application would be practicable. The answer to that question required not only an in-depth analysis of the very concept of ‘piercing’, but also of the grounds of liability of members of a sp. z o.o. company that are alternative to it as well, while simultaneously verifying if such a concept were methodologically and doctrinally permissible under Polish law. The analysis carried out in the thesis leads to a conclusion that the concept of piercing liability is possible to be received in Polish company law as it currently stands, while its application would be practicable particularly in drastic instances of abuse of a legal form of a sp. z o.o. company. However, the concept of piercing liability constitutes a solution that is in essence law-making; an instrument of last-resort to exceptionally accord protection to creditors of a sp. z o.o. company. Its unreasonable application could lead to endangering the safety of commerce and depreciation of attractiveness of a sp. z o.o. company as a business structure, in particular given the practically absolute character of that liability. For it is that in its ‘classic’ form, the concept of ‘piercing’ precludes members – in principle, due to its objective character – from escaping liability, for instance through proving the absence of fault for an act constituting an abuse of a legal form of a sp. z o.o. company. Because of this, in remarks and recommendations de lege ferenda it has been submitted that an introduction of liability of members of a sp. z o.o. company as against its creditors into Polish insolvency law should take place; by virtue of this, the protection of creditors of a sp. z o.o. company would be reinforced in the event of an abuse, while, at the same time, allowing members to be relieved of liability through giving proof that they are not culpable of any abuse.
Keywords: creditor protection; company with limited liability (a private limited company); piercing liability; lifting (piercing) the corporate veil; Durchgriffshaftung; abuse of a legal form of a company; extinguishment of existence of a company; Existenzvernichtung; undercapitalisation of a company; ‘relay race’ with companies; factual liquidation; institutional abuse; teleological reduction; purposive reduction; departure from grammatical sense of a provision; tortious liability; limitation of indemnification to directly injured; direct injury; indirect injury; Sonderverbindung; relation of a specific link; Treuepflichten; duties of loyalty